PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP BEBAN KERJA PEGAWAI DI SEKOLAH TINGGI TEKNOLOGI MIGAS DI BALIKPAPAN - Lukman Lukman (Sekolah Tinggi Teknologi MIGAS, 2022)
Quality improvement is one of the strategies that must be carried out by both business organizations and non-business organizations with an emphasis on fulfilling the wishes of members or consumers. On the other hand, organizational performance and satisfaction of members and customers is a unity that is difficult to separate. Performance has a direct effect on the level of satisfaction. Therefore, an organizational unit is expected to improve its performance, starting with knowing the level of satisfaction obtained by its members or customers. and opportunities for competition that are getting sharper with changing people's desires, technological advances, and social changes raise organizational challenges. Based on the consideration of increasing competitiveness, the organization in this case is the Balikpapan Oil and Gas College of Technology or abbreviated as STT Migas Balikpapan.Workload has a positive effect, this is known through the workload coefficients on TQM of 0.841 and has a significant effect on total quality management at STT Migas Balikpapan, this is known through the t-statistics value of 19.346 and p-value of 0.000 <0.05. This means that the workload as measured by indicators of time pressure, work schedule, role ambiguity and role conflict, noise, informant overload, temperature extremes, ergonomics aspect of workplace layout, self-esteem has been able to improve TQM as measured by indicators focus on customer, scientific approach, teamwork, continuous system, education and training, freedom in TQM, unity of TQM goals, real involvement and empowerment. The increase in the workload experienced by STT Migas Balikpapan employees will be able to increase the total quality management of STT Migas Balikpapan.